2021
DOI: 10.1177/00219983211033888
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable films from fishing industry waste: Technological properties and hygroscopic behavior

Abstract: The objective was to evaluate the effect of glycerol on functional properties and sorption behavior of films elaborated with myofibrillar proteins of fish. Analyses of solubility, water vapor permeability (WVP), tensile strength (TS), elongation, and moisture sorption isotherms were performed. Films with lower glycerol concentrations (5, 10, and 15%) showed lower (p ≤ 0.05) permeability when compared to films with 30 and 40%. The increase in the glycerol concentration decreased the TS and increased the elongat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…FGA has remarkable mechanical and barrier qualities, making it an excellent choice for biodegradable food packaging. Pereira et al [19] explored the influence of glycerol on films made from fish myofibrillar proteins. Decreased glycerol concentrations led to a decrease in the permeability of water vapor and an increase in the strength under tension.…”
Section: Introductionmentioning
confidence: 99%
“…FGA has remarkable mechanical and barrier qualities, making it an excellent choice for biodegradable food packaging. Pereira et al [19] explored the influence of glycerol on films made from fish myofibrillar proteins. Decreased glycerol concentrations led to a decrease in the permeability of water vapor and an increase in the strength under tension.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, rheological results indicate that the storage modulus and viscosity of the surimi gel increase when laver powder is added, causing a prolongation of its protein denaturation. In this direction, a recent study with biopolymers concluded that these non-Newtonian fluids were useful for producing various types of food packaging [ 16 ]. Furthermore, the study of the rheological properties of non-Newtonian fluids has applications in various fields, such as volcanology [ 17 ] y and recently in the area of 3D printing with pseudo polymers by means of a fluid rheology model, in which the parameters that influence the process are detailed: viscosity and oscillatory shear stresses [ 18 ].…”
Section: Introductionmentioning
confidence: 99%